Rancang Bangun Sistem Informasi Harga Pokok Produk Busana Muslim Dengan Metode Activity Based Costing (PT. RAMLI EKSEKUTIF) - Jefri, Muhammad; Widodo, Arifin Puji; Arifin, Mochammad (Jurnal JSIKA, 2012)
In the company there are many difficulties in recording and processing of production data as well as recording of financial transactions that occur, PT. Ramli Executive is a company that engaged in producing garment and clothing. PT. Ramli has difficulties in recording the raw materials used for the production process, labor and production process costs (overhead) used to manufacture a product, more and more developed variants Moslem-wear often experience delays in determining the cost of production. With information system, hence made a information system is expected to be a calculation tool of the cost production. This computerized information system that includes an accurate calculation of costs can increase a company´s competitive advantage. The information system is expected to generate output information in the form of cost of goods manufactured with the method of Activity Based Costing, the cost of the activity report,the  report selling prices, the raw material usage reports, and the reports of labor. Application of system production cost can be used as a basis for determining the selling price policy and to know the gross profit from a product. Keywords : Activity based costing, Harga pokok produksi, akuntansi biaya. Biaya Overhead.